Characterization of an unusual carlavirus-like RNA from papaya (Carica papaya) lacking essential genes - Milenka Vera; Raúl Cifuentes; Ronan Keener; Neil Olszewski; Robert A. Alvarez-Quinto; Diego F. Quito-Avila (PLoS ONE, 2025)
We report the characterization of a novel carlavirus-like RNA, provisionally named papaya defective virus 1 (PapDfV1), identified through high-throughput sequencing of papaya latex RNA. PapDfV1 contains two open reading frames (ORFs): ORF 1 encodes a 211.1 kDa replicase with 96% sequence identity to Zhejiang betaflexivirus 2 (ZhBV2), while ORF 2 exhibits a chimeric structure with regions homologous to two distinct ORFs of ZhBV2. Notably, PapDfV1 harbors a 2.1 kb deletion spanning the downstream portion of triple gene block (TGB) 1, the entirety of TGB2 and TGB3, capsid protein (CP), and the upstream region of the nucleic acid binding protein (NABP). Phylogenetic analysis of the replicase sequence grouped PapDfV1 with ZhBV2 and three Chinese isolates of cowpea mild mottle virus (CPMMV), two of which share the terminal regions 5’-GGAAAAACAGAA and CCTGGTTTT-3’. Mechanical inoculation and agroinfiltration failed to infect PapDfV1 in papaya, Nicotiana benthamiana, and common bean, whereas a ZhBV2 construct successfully infected soybean, common bean, and N. occidentalis. Detection of PapDfV1 in total and double-stranded RNA from leaf tissue of a 2-year-old papaya plant indicates that its replication and movement may depend on host proteins expressed in mature papaya plants or be facilitated by co-infection with unknown papaya viruses. These findings contribute to the growing body of knowledge on the existence and evolution of non-canonical virus-like RNA sequences lacking CP and other genes typically involved in virus movement.